Poster #22 - Wild animals can be a food source in Vietnam: Results from a mixed – method cross-sectional survey - Thang Nguyen-Tien; Ha Nguyen Thi Thanh; Hu Suk Lee; Sinh Dang-Xuan; Unger, Fred; Bett, Bernard K.; Hung Nguyen-Viet (Elsevier, 2025)
Background: Although wildlife farming has been promoted as a measure to enhance biodiversity conservation and as an alternative source of food and income, wild animals harbor many infectious pathogens, many of which can infect humans and livestock. In Vietnam, wildlife farming has become a major socioeconomic activity given its major contributions to income generation, food (meat) production, job creation, and economic growth.